2004
DOI: 10.1016/j.jom.2004.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The service volunteer – loyalty chain: an exploratory study of charitable not‐for‐profit service organizations

Abstract: Many not-for-profit organizations rely on volunteers to help accomplish their service objectives. Although volunteers work alongside or in some cases replace employees in the delivery of service, incorporating volunteer labor into the service delivery system of the not-for-profit poses unique challenges. Understanding these challenges represents an important foundationbuilding step in understanding the implications for service design and service operations when using volunteers. This paper identifies and descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 23 publications
6
98
0
1
Order By: Relevance
“…Although volunteer satisfaction is difficult to value, it is critical, because it directly affects volunteer retention (Wisner et al 2005). Additionally, on some routes, the reduced route times have benefitted Metro Meals on Wheels because it allowed the organization to increase the number of meals delivered by some volunteers on their routes; this represents a capacity increase for the organization, without a corresponding increase in the number of volunteers.…”
Section: Deployment At Metro Meals On Wheelsmentioning
confidence: 99%
“…Although volunteer satisfaction is difficult to value, it is critical, because it directly affects volunteer retention (Wisner et al 2005). Additionally, on some routes, the reduced route times have benefitted Metro Meals on Wheels because it allowed the organization to increase the number of meals delivered by some volunteers on their routes; this represents a capacity increase for the organization, without a corresponding increase in the number of volunteers.…”
Section: Deployment At Metro Meals On Wheelsmentioning
confidence: 99%
“…On the other hand, from employees' perspective, it is the current job and approach towards the job that lead to EL and retention. Wisner (2005) found that satisfied volunteers are more likely to remain for longer periods of time with the same organization, donate financially, and recommend the volunteer experience to others. ES and EL remained for long a challenge, and they are now critical for the industry to compete globally in terms of improving SQ and OE.…”
Section: Ei Drives Es and Elmentioning
confidence: 99%
“…Judging by the number of studies published, considerably less time and effort has been devoted to this area than to the issue of segmentation. Prominent works to emerge in this field include Bendapudi et al (1996), Webb et al (2000), Wymer and Starnes (2001), Wisner, Stringfellow, Youngdahl, and Parker (2005), Briggs et al (2007), Ranganathan and Henley (2008), Vecina, Chacón, Sueiro, andBarrón (2012), Veludo-de-Oliveira et al (2013) and Lee, Won, and Bang (2014) as well as research based on the commitment-trust model developed by Morgan and Hunt (1994), Sargeant and Lee (2004), MacMillan, Money, Money, and Downing (2005) and Sargeant et al (2006). Bendapudi et al (1996) merge relevant research on marketing, economics, sociology and social psychology in an effort to further theoretical understanding of helping behaviour and posit a model which serves as a guide for NGOs.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The works of Wisner et al (2005) and Vecina et al (2012) focus on an analysis of volunteer satisfaction. Wisner et al (2005) report a close link between volunteer satisfaction with their work and loyalty towards the organisation.…”
Section: Review Of the Literaturementioning
confidence: 99%